1970
DOI: 10.30630/jam.v13i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Praktik Good Corporate Governance Terhadap Praktik Manajemen Laba (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2017)

Abstract: Financial reports are a medium for companies to convey information about the accountability of management to the needs of external parties. Earnings management is a deliberate process of taking steps within the limits of general accounting principles both inside and outside the limits. This study aims to analyze the influence of good corporate governance consisting of independent board of directors, managerial ownership and institutional ownership on earnings management by using modified jones models with prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Penelitian-penelitian sebelumnya telah menguji manajemen laba dengan pertumbuhan penjualan (Fahmie, 2018;Juhaeriah et al, 2021;Karina & Sutandi, 2019;Sebastian & Handojo, 2019), kepemilikan institusional (Anggreni & Adiwijaya, 2020;Fahmie, 2018;Istikhomah & Widyawati, 2018;Karina & Sutandi, 2019;Zakia et al, 2019), leverage (Amin & Firmansyah, 2023;Anggreni & Adiwijaya, 2020;Arthawan & Wirasedana, 2018;Astuti et al, 2017;Puspitasari et al, 2019;N. A. Sari & Susilowati, 2021;Sebastian & Handojo, 2019), kualitas audit (Asyati & Farida, 2020;Khairunnisa et al, 2020;Lolana & Mulyani, 2019), auditor internal (Alzoubi, 2019;Anzelya & Kurniawati, 2020;Ghaleb et al, 2020;Indriswati & Triyanto, 2020;Jasman & Amin, 2017), pengungkapan tata kelola (Alam et al, 2020;Hermanto & Tjiandra, 2022;Janrosl & Lim, 2019;Maknunah & Prita, 2016;D. B. Wijaya & Firmansyah, 2021), kepemilikan manajerial (Anggraeni & Hadiprajitno, 2013;Arthawan & Wirasedana, 2018;Ayem & Ongirwalu, 2020;Zakia et al, 2019), ukuran perusahaan (Anggreni & Adiwijaya, 2020;Arthawan & Wirasedana, 2018;Astuti et al, 2017;…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Penelitian-penelitian sebelumnya telah menguji manajemen laba dengan pertumbuhan penjualan (Fahmie, 2018;Juhaeriah et al, 2021;Karina & Sutandi, 2019;Sebastian & Handojo, 2019), kepemilikan institusional (Anggreni & Adiwijaya, 2020;Fahmie, 2018;Istikhomah & Widyawati, 2018;Karina & Sutandi, 2019;Zakia et al, 2019), leverage (Amin & Firmansyah, 2023;Anggreni & Adiwijaya, 2020;Arthawan & Wirasedana, 2018;Astuti et al, 2017;Puspitasari et al, 2019;N. A. Sari & Susilowati, 2021;Sebastian & Handojo, 2019), kualitas audit (Asyati & Farida, 2020;Khairunnisa et al, 2020;Lolana & Mulyani, 2019), auditor internal (Alzoubi, 2019;Anzelya & Kurniawati, 2020;Ghaleb et al, 2020;Indriswati & Triyanto, 2020;Jasman & Amin, 2017), pengungkapan tata kelola (Alam et al, 2020;Hermanto & Tjiandra, 2022;Janrosl & Lim, 2019;Maknunah & Prita, 2016;D. B. Wijaya & Firmansyah, 2021), kepemilikan manajerial (Anggraeni & Hadiprajitno, 2013;Arthawan & Wirasedana, 2018;Ayem & Ongirwalu, 2020;Zakia et al, 2019), ukuran perusahaan (Anggreni & Adiwijaya, 2020;Arthawan & Wirasedana, 2018;Astuti et al, 2017;…”
Section: Pendahuluanunclassified
“…Pengujian yang dilakukan oleh Alam et al (2020), Hermanto & Tjiandra (2022, dan Janrosl & Lim (2019) menemukan bahwa pengungkapan tata kelola perusahaan memiliki pengaruh negatif terhadap manajemen laba. Hasil tersebut berbeda dengan temuan Maknunah & Prita (2016) dan bahwa pengungkapan tata kelola perusahaan tidak memiliki pengaruh terhadap manajemen laba. Adanya perbedaan hasil dalam penelitian-penelitian sebelumnya, maka pengujian pengungkapan tata kelola terhadap manajemen laba perlu diinvestigasi lebih lanjut.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…The institution can be in the form of government, private or foreign institutions (Widarjo, 2010). Febrina and Maryati (2018) concluded that the presence of this institutional ownership has a very large role to supervise the management and company policies. These actions can encourage managers to focus more on company performance).…”
Section: Introductionmentioning
confidence: 99%